Perilaku Solusi Pada Laju Pertumbuhan Jumlah Benih Padi Serta Luasan Area Sawah Desa Baratan - Retna Widyaningsih (UNION : Jurnal Ilmiah Pendidikan Matematika, 2018)
The aims research to find out the stages of good rice seed will be planted, to know the time calculation in Java to plant rice, and to complete the model and general mathematical solution by calculating the number of rice seeds involving the area of rice fields (10.000 m ^ 2). This type of research used qualitative research with ethnography approach. Research subjects namely Mbah and Pakde in Baratan village who work a rice farmer. This study uses interview guidelines. The results obtained from the interview data that is to determine the stage of good rice seed will be planted is to plow the field using a hoe, soaking rice seeds for 48 hours, sort the results of good rice immersion, curing for 48 hours to germinate, sow seeds evenly, after 20 days of paddy seedlings removed and planted, 1 week given urea fertilizer, 45 days fertilized again, and 3 months ready for harvest, while for the calculation of time in good Java language to plant rice that is prey ketelu on 25 August - 18 september (24 days ). The result of the mathematical model and solution associated with calculating the amount of rice involving the paddy area is obtained by the area of rice field (10.000m 2), the number of rice seeds needed is more.